SEASONAL LIFE-HISTORY OF EPILACHNA VIGINTIOCTOPUNCTATA (FABR.) (COLEOPTERA : COCCINELLIDAE) IN PUNJAB - SINGH, TARLOK; PHALOURA, S. P. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
E. vjg ¡ng joctopiinclata (Fabr.) attacks both cultivated and wild plants of families Solanaceae and Cucurbitaceae only in Punjab. It remains active from March to October and completes 6-7 broods and, its maximum infestation has been observed in March and April (temp. 26.0°C— 35.O’C, Average R. H. 56.003±15.23%) and, August to October (temp. 25.5°C—33.4°C, Average R. H. 61.796 ± 6.837%). The total period from egg to adult of spring brood (21—25 days) is shorter than that of autumn brood (28—33 days). In competition with Aulacop hora Jove (colic Lucas, it normally stays away.